Fraud Pentagon Theory dalam Mendeteksi Fraudulent Financial Reporting Pada Perusahaan yang Terdaftar di Jakarta Islamic Index 70 (JII 70) Tahun 2018 - Khoirunnisa, Awaliyatu; Rahmawaty, Anita; Yasin, Yasin (BISNIS, 2020)
This study aims to detect fraudulent financial reporting through fraud pentagon theory in companies listed in the Jakarta Islamic index 70. The research method used is quantitative research with a comparative causal approach. Related to sampling using purposive sampling. The findings in this study are the financial target variables, external pressure, nature of industry and rationalization have a significant effect on the detection of financial statement fraud. As for financial stability, ineffective monitoring, change in auditors, change of director, and arrogancy do not have a significant effect on the detection of financial statement fraud.